2018
DOI: 10.1108/jfra-09-2017-0087
|View full text |Cite
|
Sign up to set email alerts
|

Information content and informativeness of analysts’ report: evidence from Malaysia

Abstract: Purpose This study aims to document the influence of information content and the informativeness of analyst reports towards cumulative abnormal return in the Malaysian market. Design/methodology/approach Samples of analyst reports for the period 4th January 2010 until 24th December 2015 were collected from the Bursa Malaysia’s repository system for daily basis information. The study uses market-adjusted method for the calculation of cumulative abnormal return and panel regression to test the research objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In line with Zadeh et al (2016), Mohd Thas Thaker et al (2018 concluded that the risk information provided is insufficient in Malaysia. The study employed a market-adjusted method to calculate cumulative abnormal return (CAR) and panel regression to test the influence of information content and the informativeness of analyst reports towards CAR in the Malaysian market.…”
Section: Risk Reporting and Disclosurementioning
confidence: 61%
See 1 more Smart Citation
“…In line with Zadeh et al (2016), Mohd Thas Thaker et al (2018 concluded that the risk information provided is insufficient in Malaysia. The study employed a market-adjusted method to calculate cumulative abnormal return (CAR) and panel regression to test the influence of information content and the informativeness of analyst reports towards CAR in the Malaysian market.…”
Section: Risk Reporting and Disclosurementioning
confidence: 61%
“…The scope of risk disclosure seen in annual reports of Malaysian companies is limited, with a glaring paucity of key information (Amran et al, 2008;Zadeh et al, 2016). The applicability of analyst reports is, therefore, questionable as the details presented have frequently been found wanting in explaining stock returns (Mohd Thas Thaker et al, 2018). These observations lend credence to the view that risk information obtained from companies' public reports is hardly relevant to investors' decision making (Rajgopal, 1999;Amran et al, 2008;Anagnostopoulos and Skordoulis, 2011;Zadeh et al, 2016;Mohd Thas Thaker et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As young age firms are relatively new in the market, their ROE tends to increase slowly, subsequently influencing the return of stock in a positive way. Furthermore, investors usually target young growth stocks for investment purposes as these stocks tend to have increased stability with marginal increases (Mantri, 2008). Although ROE is in favor of young age firm, those firms also face higher risk.…”
Section: Panel Data Analysis For Young Aged Firmsmentioning
confidence: 99%